Development of Store Atmosphere on Culinary Efforts to Increase Interest in The Buying Public in District of Percut Sei Tuan - Nel Arianty, S.E., M.M. (KUMPULAN JURNAL DOSEN UNIVERSITAS MUHAMMADIYAH SUMATERA UTARA)
-